Penerapan Model Pembelajaran Contextual Teaching and Learning (CTL) Untuk Meningkatkan Prestasi Belajar Siswa - Suriswo; Sumartono (Cakrawala: Jurnal Pendidikan, 2021)
In general , the purpose of this research is to apply a learning model that can improve student achievement . Specifically, the objectives of this study are to: (1). Know and analyze the learning conditions in SD Kagok before applying the CTL learning model. (2). Analyzing the effectiveness of the CTL learning model can improve student achievement which is higher than previous learning outcomes that are not using the CTL learning model at SD Negeri Kagok. Slawi District, Tegal Regency. Knowing the form of support from the principal, other teachers and facilities in the implementation of the CTL learning model. This research method uses a pre and post test experimental design. This phase includes several activities, namely; (a) conducting a pretest (pretest), (b) conducting an observation, interview/interview, (c) conducting a final test (posttest). Conducting a pretest (pretest) to one group/class before applying the CTL model. Conducting a final test (posttest) to the group/class after applying the CTL model. Perform analysis by comparing pre-test and post-test scores with t-test. From the results of calculations using the t-test, it is obtained that the empirical t-test is greater than the t-test in the table, so it can be concluded that the CTL learning model is more effective.